Health assessment in nursing - Weber, Janet R.; Kelley, Jane (Philadelphia, Pennsylvania : Wolters Kluwer Health/Lippincott Williams & Wilkins, 2014)
Health Assessment in Nursing, 5th edition, provides all of the background needed for interviewing the client and performing assessment making this the perfect text for students learning Assessment. The unique 3-column format used for teaching students assessment techniques (Assessment Procedures/Normal Findings/Abnormal Findings) breaks the process down into easy-to-understand units. The COLDSPA mnemonic (Character, Onset, Location, Duration, Severity, Pattern, and Associated Factors) provides logical structure for the patient interview helping students to remember the most essential questions to ask a client. A new chapter "Psychosocial, Cognitive, and Moral Development" focuses on those areas of development for young adults, middle-age adults, and older adults ensuring that the nurse will perform a holistic nursing assessment. New integrated case study guides students through the assessment process helping them to develop the diagnostic reasoning skills every nurse needs. New Evidence-Based Practice Health Promotion and Disease Prevention boxes include Healthy People 2020 goals ensuring best practice. The new art program and interior design enhance readability allowing students to develop the necessary skills needed to perform accurate and timely health assessments"--Publisher's description
Nursing data collection, documentation, and analysis -- Nurse's role in health assessment: collecting and analyzing data -- Collecting subjective data: the interview and health history -- Collecting objective data: the physical examination -- Validating and documenting data -- Thinking critically to analyze data and make informed nursing judgments -- Integrative holistic nursing assessment : Assessing mental status and substance abuse -- Assessing psychosocial, cognitive, and moral development -- Assessing general status and vital signs -- Assessing pain: the 5th vital sign -- Assessing for violence -- Assessing culture -- Assessing spirituality and religious practices -- Assessing nutritional status -- Nursing assessment of physical systems : Assessing skin, hair, and nails -- Assessing head and neck -- Assessing eyes -- Assessing ears -- Assessing mouth, throat, nose, and sinuses -- Assessing thorax and lungs -- Assessing breasts and lymphatic system -- Assessing heart and neck vessels -- Assessing peripheral vascular system -- Assessing abdomen -- Assessing musculoskeletal system -- Assessing neurological system -- Assessing male genitalia and rectum -- Assessing female genitalia and rectum ' Pulling it all together: integrated head-to-toe assessment -- Nursing assessment of special groups -- Assessing childbearing women -- Assessing newborns and infants -- Assessing children and adolescents -- Assessing older adults -- Assessing families -- Assessing communities -- Appendices : Nursing historical guide -- Physical assessment guide -- NANDA approved nursing diagnoses 2012-2014 -- Selected collaborative problems -- Canada's food guide --
Includes index.
Keywords: DIAGNOSTICS INFIRMIERS